Working Capital Management and Profitability: evidence from top listed companies in Malaysia - Sharifah Nur Asykeen El Edrus, Bt. Wan Habib Ismail (Universiti Malaysia Sarawak, UNIMAS, 2011)
This research study examines the effects of working capital management towards the firms’ profitability of 100 top Malaysian listed firms’ on the Main Board of Bursa Malaysia over the period 2004 -2009. The empirical part of the study investigates 64 top listed firms over the period 2004 -2009 and the financial data are extracted from Thomson DataStream data base and companies’ annual reports. Debt ratio and size of firms have been used as control variables. On the overall basis, the findings show that, by using Pearson correlation and regression analysis (general least square with cross-section weight models), this results indicate that firms’ profitability in Malaysia have substantially been affected by cash conversion cycle, leverage (the used of debt) and firm size. First, the evidence found that that there is a significant negative association between profitability and the cash conversion cycle. When the cash conversion cycle increased, the profitability of the firm will decrease. However, the evidence found that there is no significant relationship at all between the firm’s profitability with current ratio. Besides, this research study also found that the profitability of the firm has significant negative relationship with leverage (the used of debt). There is also positive relationship between the size of firm and its profitability.